Quantitative Optical Coherence Elastography for Robust Stiffness Assessment - Xuan Liu; Farzana Zaki; Yahui Wang (Applied Sciences, 2018)
We demonstrated the capability of quantitative optical coherence elastography (qOCE) for robust assessment of material stiffness under different boundary conditions using the reaction force and displacement field established in the sample.